Converting Step-Growth to Chain-Growth Condensation Polymerization - Yokoyama, A.; Yokozawa, T.
The development and applications of chain-growth condensation polymerization are reviewed. Well-defined aromatic polyamides, polyesters, and polyethers have been synthesized via substituent effect-assisted chain-growth condensation polymerization, in which the polymer propagating ends are more reactive than the monomers due to resonance or inductive effects between the functional groups of the terminal monomer units. Chain-growth condensation polymerization for the synthesis of aromatic polyamides has been applied to the construction of well-defined block copolymers and star-shaped polymers. Nickel-catalyzed condensation polymerization of 5-metalated 2-halothiophene has been found to proceed in a chain-growth polymerization manner. Detailed investigations revealed that this polymerization is a catalyst-transfer ondensation polymerization, in which the chain-growth nature is attributable to intramolecular catalyst transfer. Phase-transfer polymerization in a solid-solution biphasic system, in which the monomers are stored in an unpolymerizable solid phase, has been applied to the chain-growth condensation polymerization of potassium 4-bromomethyl-2- octyloxybenzoate.